Managing and treating per‐ and polyfluoroalkyl substances (PFAS) in membrane concentrates - Tow, Emily W.; Ersan, Mahmut Selim; Kum, Soyoon; Lee, Tae; Speth, Thomas F.; Owen, Christine; Bellona, Christopher; Nadagouda, Mallikarjuna N.; Mikelonis, Anne M.; Westerhoff, Paul; Mysore, Chandra; Frenkel, Val S.; et al. (AWWA water science, 2021)
Per‐ and polyfluoroalkyl substances (PFAS), which are present in many waters, have detrimental impacts on human health and the environment. Reverse osmosis (RO) and nanofiltration (NF) have shown excellent PFAS separation performance in water treatment; however, these membrane systems do not destroy PFAS but produce concentrated residual streams that need to be managed. Complete destruction of PFAS in RO and NF concentrate streams is ideal, but long‐term sequestration strategies are also employed. Because no single technology is adequate for all situations, a range of processes are reviewed here that hold promise as components of treatment schemes for PFAS‐laden membrane system concentrates. Attention is also given to relevant concentration processes because it is beneficial to reduce concentrate volume prior to PFAS destruction or sequestration. Given the costs and challenges of managing PFAS in membrane concentrates, it is critical to evaluate both established and emerging technologies in selecting processes for immediate use and continued research. Article Impact Statement Readers will benefit from learning about established and emerging management approaches for per‐ and polyfluoroalkyl substances and the peculiarities of their application to reverse osmosis and nanofiltration concentrates.